THE TIREDNESS SOCIETY IN THE POST-PANDEMIC BRAZILIAN CONTEXT - Calegari, Ana Elisa Silva; Doti, Marcelo Micke (Revista Interface Tecnológica, 2022)
In the post-pandemic Brazilian context, the state of fatigue and exhaustion of workers is urgent, in face of demands, pressure for results, demand for high performance, also marked by individual self-demands and people’s difficulties in disconnecting from the service and/or having more time to do what they like in their playfulness. Companies want to produce more with fewer resources, recover the resulting losses and unachieved goals, resulting from the period in which activities were stopped. Philosophical and cultural contributions shed light on the subject and relate it to the evolution of business management itself, to neoliberalism and to the existing imbalance between theory and practice, aggravated by crises and diseases. Is there a limit to working without getting sick? That said, a bibliographic review can boost a critical and awareness-raising look at the impacts on the physical and mental health of workers and think of suggestions for conciliation and improvement between managers and subordinates, since tiredness represents a problem for organizations and for the society as well. The research sources are electronic works and reports on the subject, accompanied by the analysis and interpretation of the data found.